President’s Welcome and Address - Dushanka V. Kleinman, DDS, MScD (Blackwell Synergy, 2000)
What a delight it is to welcome you to the 62nd annual meeting of the American Association of Public Health Dentistry in Honolulu, Hawaii! We are convening on the beautiful island of Oahu, home to about 80 percent of our youngest stateÃƒÂ¢Ã¢â€šÂ¬Ã¢â€žÂ¢s population and appropriately known as the ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œGathering Place.ÃƒÂ¢Ã¢â€šÂ¬Ã‚Â